DEVELOPMENT OF THE METHODS AND TOOLS OF CHECKING OF CURRENT-TYPE AND DISTANCE-TYPE OUT-OF-STEP PROTECTION - I. Litvinov; A. Marchenko (Вестник Северо-Кавказского федерального университета, 2022)
The article presents the approach to simulate instantaneous currents and voltage during out-of-step operation of a power system. These electrical signals then can be used to conduct commissioning of out-ofstep protection. A graphical representation of the simulation results simplifies the process of selecting model parameters for checking the out-of-step protection (one based on current-oscillations and distance once). The results of transient simulation are saved in the international waveform recording format COMTRADE, which makes it possible to carry out comprehensive verification of emergency control equipment without reference to the testing equipment of a particular manufacturer.